2017
DOI: 10.2147/ott.s147586
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA NEAT1 contributes to paclitaxel resistance of ovarian cancer cells by regulating ZEB1 expression via miR-194

Abstract: BackgroundChemoresistance is one of the major obstacles for cancer therapy in the clinic. Nuclear paraspeckle assembly transcript 1 (NEAT1) has been reported as an oncogene in most malignancies such as lung cancer, esophageal cancer, and gastric cancer. This study is designed to investigate the function of NEAT1 in paclitaxel (PTX) resistance of ovarian cancer and its potential molecular mechanism.Patients and methodsThe expressions of NEAT1 and miR-194 in ovarian cancer tissues and cells were estimated by qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
112
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(122 citation statements)
references
References 32 publications
10
112
0
Order By: Relevance
“…10 A member of the lncRNA, nuclear enriched abundant transcript 1 (NEAT1) is reported as an oncogene in various malignant tumors, including hepatocellular carcinoma, non-small cell lung cancer, nasopharyngeal carcinoma, breast cancer and OC. [11][12][13][14][15][16] report that NEAT1 contributed Yangcheng Liu and Yong Wang contributed equally to this work. to paclitaxel (PTX) resistance of OC cells through upregulating ZEB1 expression by sponging of .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…10 A member of the lncRNA, nuclear enriched abundant transcript 1 (NEAT1) is reported as an oncogene in various malignant tumors, including hepatocellular carcinoma, non-small cell lung cancer, nasopharyngeal carcinoma, breast cancer and OC. [11][12][13][14][15][16] report that NEAT1 contributed Yangcheng Liu and Yong Wang contributed equally to this work. to paclitaxel (PTX) resistance of OC cells through upregulating ZEB1 expression by sponging of .…”
Section: Introductionmentioning
confidence: 98%
“…A member of the lncRNA, nuclear enriched abundant transcript 1 (NEAT1) is reported as an oncogene in various malignant tumors, including hepatocellular carcinoma, non‐small cell lung cancer, nasopharyngeal carcinoma, breast cancer and OC . An (2017) report that NEAT1 contributed to paclitaxel (PTX) resistance of OC cells through upregulating ZEB1 expression by sponging of microRNA‐194 (miR‐194) . Ding (2017) report that NEAT1 promoted OC cells’ proliferation and apoptosis through regulation of microRNA‐34a‐5p (miR‐34a‐5p)/B‐cell lymphoma‐2 (BCL2) .…”
Section: Introductionmentioning
confidence: 99%
“…Downregulation of ZEB1 has been found to inhibit EMT of ovarian cancer cells [12]. ZEB1 also acts as the target of miRs, mediating the inhibitory effect on EMT of ovarian cancer cells [8, 10, 14]. Dysregulation of ZEB1 is also involved in emodin-induced inhibition of EMT in epithelial ovarian cancer cells [13].…”
Section: Discussionmentioning
confidence: 99%
“…ZEB1 functions as an inducer of tumor invasion, metastasis, and resistance to chemo- and radiotherapy, in large part by mediating the epithelial to mesenchymal transition (EMT) in cancer cells [7]. In ovarian cancer, it has been found that ZEB1 expression increases and ZEB1 upregulation mediates the chemoresistance induced by several long noncoding RNAs and microRNAs (miRs) [8-11]. It is also reported that downregulation of ZEB1 inhibits EMT of ovarian cancer cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…Drug resistance has been a major reason for the failure of chemotherapy. Particularly, resistance to paclitaxel (PTX) has been one of the primary causes of chemotherapy resistance in clinical therapeutic applications of ovarian carcinoma for a long time . PTX is a natural medication used as the first‐line chemotherapeutic agent for the treatment of OC because it does not induce cross‐resistance with platinum‐based drugs .…”
Section: Introductionmentioning
confidence: 99%